2020
DOI: 10.3390/pathogens9120988
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and Vaccine Coverage of Streptococcus Pneumoniae Colonization in the Nasopharynx of Thai Children in Congested Areas in Chiang Mai

Abstract: Streptococcus pneumoniae causes around 10% of all deaths in children younger than five years of age. This study aimed to examine the serogroups/serotypes of S. pneumoniae colonization and vaccine serotype coverage of this organism among Thai children. Nasopharyngeal swabs of children less than or equal to 15 years of age were obtained in congested areas in Chiang Mai from 1 February 2013 to 1 August 2013. The serotyping of S. pneumoniae isolates was performed using the ImmuLex™ kit and the vaccine serotype cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In this study, the PNC non-susceptible rate among the 309 S. pneumoniae isolates was as high as 81.6% (63.2% intermediate and 18.4% resistant), but the CTX non-susceptible rate was only 14.2% (11.6% intermediate and 2.6% resistant). The ETM and AZM resistance rates among the 309 S. pneumoniae isolates were 95.8 and 96.1%, which are similar to those from Western China (94.3%), North China (95–98.2%), and Southwest China (99.1%) ( Zhao et al, 2020 ; Liang et al, 2021 ; Yan et al, 2021 ; Zhou et al, 2022 ) but significantly higher than those from Southeast Asia (38.5–42.0%), India (37.0%), United States (37.1%), and Latin America (43.2%) ( Mendes et al, 2016 ; Singh et al, 2017 ; Moreno et al, 2020 ; Wangirapan et al, 2020 ; Dzaraly et al, 2021 ). In addition, 96.1% of the 309 S. pneumoniae isolates in this study showed different multidrug resistance patterns, which is also similar to those from Western China (93.8%) ( Liang et al, 2021 ), but significantly higher than those from South Korea (46.2%), Malaysia (18.0%), and Latin America (44.3%) ( Park et al, 2019 ; Moreno et al, 2020 ; Dzaraly et al, 2021 ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In this study, the PNC non-susceptible rate among the 309 S. pneumoniae isolates was as high as 81.6% (63.2% intermediate and 18.4% resistant), but the CTX non-susceptible rate was only 14.2% (11.6% intermediate and 2.6% resistant). The ETM and AZM resistance rates among the 309 S. pneumoniae isolates were 95.8 and 96.1%, which are similar to those from Western China (94.3%), North China (95–98.2%), and Southwest China (99.1%) ( Zhao et al, 2020 ; Liang et al, 2021 ; Yan et al, 2021 ; Zhou et al, 2022 ) but significantly higher than those from Southeast Asia (38.5–42.0%), India (37.0%), United States (37.1%), and Latin America (43.2%) ( Mendes et al, 2016 ; Singh et al, 2017 ; Moreno et al, 2020 ; Wangirapan et al, 2020 ; Dzaraly et al, 2021 ). In addition, 96.1% of the 309 S. pneumoniae isolates in this study showed different multidrug resistance patterns, which is also similar to those from Western China (93.8%) ( Liang et al, 2021 ), but significantly higher than those from South Korea (46.2%), Malaysia (18.0%), and Latin America (44.3%) ( Park et al, 2019 ; Moreno et al, 2020 ; Dzaraly et al, 2021 ).…”
Section: Discussionmentioning
confidence: 70%
“…In addition, serotypes 12F, 3, 23A, 19A, 10A, 6C, and 22F and serotypes 3, 19A, and 11A were the commonly found among the S. pneumoniae isolates from Japan and South Korea, respectively ( Park et al, 2019 ; Heo et al, 2020 ; Yanagihara et al, 2021 ). Furthermore, 23F, 19F, 19A, and 14 were the predominant pneumococcal serotypes found in Thailand and Malaysia ( Wangirapan et al, 2020 ; Dzaraly et al, 2021 ). In India, 14, 1, and 19F acted as the predominant serotypes of S. pneumoniae ( Singh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation